PENGARUH KESADARAN WAJIB PAJAK DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK - Nurul Yusyawiru (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The purpose of this study was to determine the effect of taxpayer awareness, and service quality at the level of taxpayer compliance in paying taxes on motor vehicle at Tanjungpinang. The sampling method used was accidental sampling method, while the data collected through the questionnaire technique. The sample used in this study was 100 respondents. The data analysis technique used is multiple linear regression analysis techniques. The results showed that simultaneous taxpayer awareness and service quality has positive effect on tax compliance